2022
DOI: 10.1108/bfj-02-2022-0097
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the relationship between intrinsic and extrinsic product attributes with customer satisfaction: implications for food products

Abstract: PurposeThis research aims to investigate intrinsic and extrinsic product attributes as well as the relationship between these features and customer satisfaction by confirming the moderating role of competitive intensity.Design/methodology/approachThe study is conceptual and exploratory in nature, drawing on current literature and real-time experience with conceptual framework development. The information was gathered by the face-to-face survey conducted with a sample of products, specialists and customers of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 63 publications
(121 reference statements)
0
7
0
1
Order By: Relevance
“…Consumer decisions to purchase products are greatly influenced by the satisfaction felt by consumers. Greater satisfaction should be associated with increased product purchase intentions or loyalty (Sánchez García and Curras-Perez 2019) in line with (Malekpour, Yazdani, and Rezvani 2022) and also in the study by (Garcia et al, 2020) found the correspondence between satisfaction and purchase intentions can be explained by the strengths or weaknesses with which individuals hold their satisfaction or dissatisfaction. The findings of this investigation align with the study carried out by (Watanabe et al, 2019) Satisfaction is a feeling that arises as a result of achievements and expectations.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Consumer decisions to purchase products are greatly influenced by the satisfaction felt by consumers. Greater satisfaction should be associated with increased product purchase intentions or loyalty (Sánchez García and Curras-Perez 2019) in line with (Malekpour, Yazdani, and Rezvani 2022) and also in the study by (Garcia et al, 2020) found the correspondence between satisfaction and purchase intentions can be explained by the strengths or weaknesses with which individuals hold their satisfaction or dissatisfaction. The findings of this investigation align with the study carried out by (Watanabe et al, 2019) Satisfaction is a feeling that arises as a result of achievements and expectations.…”
Section: Discussionmentioning
confidence: 64%
“…Contentment is an assessment of the degree to which products, services, and the general customer encounter fulfill customer anticipations (Sheeraz Shamsi, Sablu Khan, and Mohd Afaq Khan 2023). Contentment is characterized as a gauge of customer gratification with the organization's products, services, and abilities (Malekpour et al, 2022). Contentment data, including appraisals and rankings, can assist companies in identifying the finest choices for enhancing or altering products and services (Garcia et al, 2020).…”
Section: Satisfactionmentioning
confidence: 99%
“…Los resultados encontrados muestran la importancia de considerar las preferencias individuales y la satisfacción del consumidor al desarrollar productos innovadores. Al respecto, Malekpour et al (2022) mencionaron que para ofertarlos es preciso evaluar la situación competitiva y ofrecer atributos adecuados, según las preferencias del cliente potencial.…”
Section: Resultados Y Discusiónunclassified
“…Our research applied a stated preference methodology using the BWS approach. This method investigates individual preferences in a hypothetical context by asking respondents to evaluate and choose the 'best' and the 'worst' options in multiple-choice situations, allowing the 'importances' of the attributes to be measured (Cohen 2003;Louviere et al 2015).…”
Section: Discussionmentioning
confidence: 99%